A construção, consolidação e o espetáculo do poder no México revolucionário The construction, consolidation and power spectacle in revolutionary Mexico - Carlos Alberto Sampaio Barbosa (Diálogos, 2010)
A proposta central deste artigo é analisar a construção de uma dimensão visual dos eventos políticos mexicanos entre os anos de 1900 e 1940 através da interpretação do álbum História Grafica de la Revolución Mexicana de Gustavo Casasola. Privilegiamos alguns tópicos de interpretação: os últimos dez anos do governo de Porfírio Díaz; a política no contexto da luta armada; o período da institucionalização da revolução; as solenidades políticas de eleição e posse; e a violência política. The chief goal of this article is to analyze the construction of a visual dimension of Mexican political events between 1900 and 1940 through the interpretation of Historia Grafica de la Revolución Mexicana, an album published by Gustavo Casasola. Certain topics of interpretation have been underlined: the last ten years of the Porfírio Díaz administration, politics in the context of armed strife, the institutionalization period of the revolution, the political celebrations of polls and inauguration, and political violence.